Notch1 activity in the olfactory bulb is odour‐dependent and contributes to olfactory behaviour. (19th September 2014) - Brai, Emanuele; Marathe, Swananda; Zentilin, Lorena; Giacca, Mauro; Nimpf, Johannes; Kretz, Robert; Scotti, Alessandra; Alberi, Lavinia
Abstract Notch signalling plays an important role in synaptic plasticity, learning and memory functions in both Drosophila and rodents. In this paper, we report that this feature is not restricted to hippocampal networks but also involves the olfactory bulb (OB). Odour discrimination and olfactory learning in rodents are essential for survival. Notch1 expression is enriched in mitral cells of the mouse OB. These principal neurons are responsive to specific input odorants and relay the signal to the olfactory cortex. Olfactory stimulation activates a subset of mitral cells, which show an increase in Notch activity. In Notch1cKOKln mice, the loss of Notch1 in mitral cells affects the magnitude of the neuronal response to olfactory stimuli. In addition, Notch1cKOKln mice display reduced olfactory aversion to propionic acid as compared to wildtype controls. This indicates, for the first time, that Notch1 is involved in olfactory processing and may contribute to olfactory behaviour.